A Comparison of Test Methods for Determination of Flexural Strength in Urea Model Ice - Borland, Sharon L. (1990)
Laboratory tests were performed in a basin to compare the flexural strength of urea ice obtained by three different beam test methods. The beam test used were in the in-situ three-point loaded simple beam test, the out-of- water three-point loaded simple beam test and the in-situ cantilever beam test. There is essentially no difference in flexural strength determined from either of the three-point beam test is also approximately equal to the value determined from the in-situ cantilever beam test. A reduction in flexural strength with increases in beam length-to-thickness ratio was observed for portions of the data set. Keywords: Cantilever beam test, Flexural strength, Laboratory tests, Model ice, Simple beam test, Urea ice.